Turbidity Currents - Lodh, Rajashree; Bhattacharya, Amartya Kumar (Indian Journal of Power and River Valley Development, 2020)
India’s water resources become increasingly strained, as the population of India continues to expand. Discharge of untreated sewage is the single most important cause for pollution of surface and groundwater in India. Heavy pollution from open sewers is common place in urban areas and arsenic contamination of groundwater continues to threaten the health and well-being of local communities. India is defined as a ‘water stressed’ country and innovative methods to provide cost-effective water treatment to communities are a crucial requirement if growing populations are to be sustainable. Sewage are to be removed by applying different sewage treatments. A natural river continually picks up waste products from and drops them on its bed throughout its course. Knowledge of sediment transport can be applied extensively in civil engineering such as to plan how to control the flow of water in culverts, over spillways, below pipelines and around bridge piers and abutments, excess of which can damage the environment and failure of foundation of the structures. Moreover, when suspended load of sediment is substantial due to human activities, it can cause environmental hazards including filling up of the channels by siltation. Sediment transport is the movement of organic and inorganic particles by water. In general, the greater the flow is, the more sediment will be conveyed. Water flow can be strong enough to suspend particles in the water column as they move downstream, or simply push them along the bottom of a waterway. Transported sediment may include mineral matter, chemicals and pollutants, and organic material. The total load includes all particles moving as bed load, suspended load, and wash load.